Τhe effect of the religious attitudes on the death attitudes and death anxiety in elderly intensive care patients: a cross-sectional study - Menekli, Tuğba; Doğan, Runida (Health & Research Journal, 2021)
Background: Negative death attitudes and death fear were reported at a high level among intensive care patients. Research indicates that nurses should know the factors affecting the death attitudes and death anxiety in intensive care patients to reduce these high levels of anxiety and negative attitudes. Religions have a strong relationship with death. Aim: This cross-sectional study was conducted to determine the effect of religious attitudes on death attitudes and death anxiety in elderly intensive care patients. Methods: The data of the study were collected between January 2019 and January 2020 in the intensive care unit of a university hospital in a province located in the east of Turkey. A total of 185 elderly patients participated in the study. Patient Identification Form, Ok-Religious Attitude Scale (ORAS), the Death Anxiety Scale (DAS), and Death Attitudes Profile-Revised (DAP) were used for data collection. IBM SPSS version 25.0 was used for data analysis. Results: Most of the patients (88.6%) were at high level of self-reported religious attitudes. The mean DAS score of the patients was 9.02 ± 1.64, DAP was 120.40 ± 23.70, and ORAS was 31.25 ± 2.90. According to regression analysis, the increase in ORAS scores decreased the DAS score and increased the DAP score (p <0.05). Conclusion: There was a negative relationship between religious attitudes and death anxiety and a positive relationship between religious attitudes and attitudes towards death in elderly patients in intensive care units. Nurses should evaluate the patients’ religious attitudes while they plan interventions to reduce patients’ death anxiety or to develop positive attitudes toward death in these patients.